The accuracy of electrocardiographic Q waves for the detection of prior myocardial infarction as assessed by a novel standard of reference - Hurst, Willis (Clin Cardiol, 2006)
Background: The electrocardiogram (ECG) is valuable for the identification of prior myocardial infarction (MI) in individuals participating in epidemiologic studies or undergoing screening examinations. Although the Minnesota Code, a set of criteria for the interpretation of ECGs in such situations, is commonly used to identify MI in these settings, its accuracy is incompletely understood. Hypothesis: We sought to test the accuracy of the Minnesota Code Q and QS criteria for MI against a new standard of reference, the presence of a perfusion defect on a resting myocardial scintigraphic image. Methods: The resting myocardial scintigrams of all patients studied in our nuclear cardiology laboratory during 7 consecutive months were screened for the presence of perfusion defects. For each patient with such a defect, two individuals examined on the same day, who had no perfusion defect, were selected as controls. Electrocardiograms recorded within 30 days of the scintigraphy were read blindly by two of the authors using the Minnesota Code criteria for Q or QS waves indicative of MI. Results: For 214 patients selected on the basis of their scintigraphic findings, a satisfactory ECG recorded within a month of the scintigraphy was also available. The overall sensitivity of the Q or QS criteria was 0.58 and the specificity was 0.75. As might be expected when only the most stringent criteria were applied, sensitivity was least and the specificity best. Conclusions: As in previous studies, in which necropsy material served as the standard of reference, sensitivity of the Q and QS criteria contained in the Minnesota Code is relatively modest and specificity is reasonable but not outstanding.